Posted by **Chris** on Thursday, April 25, 2013 at 11:42am.

Which expression is equivalent to (sin x + 1)(sin x − 1)?

A.

cos2^x

B.

-cos2^x

C.

cos2^x + 1

D.

cos^2x − 1

E.

-cos^2x + 1

- Calc -
**Steve**, Thursday, April 25, 2013 at 11:47am
that would be (B)

## Answer This Question

## Related Questions

- Math - Calculus - The identity below is significant because it relates 3 ...
- maths - Choose the option that gives an expression for the indefinite integral...
- Algebra 2/ Trigonometry - The expression oos² θ/sin θ + sin θ is ...
- Mathamatics - Solve the following trigonometry identities. a) 1-cos2(theta) = ...
- Math/Trigonometry - 1. Solve: 2 cos² x - 3 cos x + 1 = 0 for 0 ≤ x < ...
- trig help much appreciated! :)) - 1. Find the complete exact solution of sin x...
- Maths - if in a triangle ABC m angle A=π/2, then value of cos2 A + cos2 B...
- Pre Calculus - Use one of the identities cos(t + 2ðk) = cos t or sin(t + 2ðk) = ...
- Pre Calculus - Use one of the identities cos(t + 2ðk) = cos t or sin(t + 2ðk) = ...
- Trig check my work please? - 8 sin²(3x) cos²(3x) = 2 [2 sin(3x) cos(3x)]² = 2 [...

More Related Questions